The effect of rate of weight loss on long‐term weight regain in adults with overweight and obesity. (27th January 2016) - Vink, Roel G.; Roumans, Nadia J. T.; Arkenbosch, Laura A. J.; Mariman, Edwin C. M.; van Baak, Marleen A.
Abstract : Objective: To investigate the effect of rate of weight loss, with similar total weight loss, on weight regain in individuals with overweight and obesity. Methods: Fifty‐seven participants (BMI: 28‐35 kg/m 2 ) underwent a dietary intervention (DI). They were randomized to a low‐calorie diet (LCD; 1250 kcal/day) for 12 weeks (slow weight loss) or a very‐low‐calorie diet (VLCD; 500 kcal/day) for 5 weeks (rapid weight loss) (weight loss (WL) period) followed by a 4‐week weight‐stable (WS) period and 9 months follow‐up. Body weight and body composition (BodPod) were determined at study start and after each period. Results: Weight change was similar in both groups after WL (LCD: −8.2 kg and VLCD: −9.0 kg, P = 0.24). Weight regain after follow‐up was not significantly different between groups (LCD: 4.2 kg and VLCD: 4.5 kg, P = 0.73). Percentage fat‐free mass loss (%FFML) was higher in the VLCD‐group compared to the LCD‐group after DI (8.8% and 1.3%, respectively, P = 0.034) and was associated with weight regain during follow‐up in the whole group ( r = 0.325, P = 0.018). Conclusions: The present study showed that, with similar total weight loss, rate of weight loss did not affect weight regain. However, %FFML after DI was associated with weight regain.